Development of Innovative Pediocin PA-1 by DNA Shuffling among Class IIa Bacteriocins - Tominaga, Tatsuya (American Society for Microbiology, 2007)
Pediocin PA-1 is a member of the class IIa bacteriocins, which show antimicrobial effects against lactic acid bacteria. To develop an improved version of pediocin PA-1, reciprocal chimeras between pediocin PA-1 and enterocin A, another class IIa bacteriocin, were constructed. Chimera EP, which consisted of the C-terminal half of pediocin PA-1 fused to the N-terminal half of enterocin A, showed increased activity against a strain of Leuconostoc lactis isolated from a sour-spoiled dairy product. To develop an even more effective version of this chimera, a DNA-shuffling library was constructed, wherein four specific regions within the N-terminal half of pediocin PA-1 were shuffled with the corresponding sequences from 10 other class IIa bacteriocins. Activity screening indicated that 63 out of 280 shuffled mutants had antimicrobial activity. A colony overlay activity assay showed that one of the mutants (designated B1) produced a >7.8-mm growth inhibition circle on L. lactis, whereas the parent pediocin PA-1 did not produce any circle. Furthermore, the active shuffled mutants showed increased activity against various species of Lactobacillus, Pediococcus, and Carnobacterium. Sequence analysis revealed that the active mutants had novel N-terminal sequences; in active mutant B1, for example, the parental pediocin PA-1 sequence (KYYGNGVTCGKHSC) was changed to TKYYGNGVSCTKSGC. These new and improved DNA-shuffled bacteriocins could prove useful as food additives for inhibiting sour spoilage of dairy products.